2008
DOI: 10.1021/bm8004676
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Polyethylenimine Grafted N-Maleated Chitosan for Gene Delivery: Properties and In Vitro Transfection Studies

Abstract: To develop chitosan-based efficient gene vectors, chitosans with different molecular weights were chemically modified with low molecular weight polyethylenimine. The molecular weight and composition of polyethylenimine grafted N-maleated chitosan (NMC-g-PEI) copolymers were characterized using gel permeation chromatography (GPC) and (1)H NMR, respectively. Agarose gel electrophoresis assay showed that NMC-g-PEI had good binding ability with DNA, and the particle size of the NMC-g-PEI/DNA complexes was 200-400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 47 publications
(69 reference statements)
3
64
0
Order By: Relevance
“…Transfection efficiencies have been reported in epithelial cells using PEI [17], PEI grafted N-maleated chitosan copolymers [18], nanostructured lipid carrier with cetylated PEI and Lipofectamine 2000 [19], cationic gemini lipids [20], and poly(disulfide amine)s [21]. A comparison study using lung tumor and normal epithelial cells showed that Lipofectamine 2000 (cationic lipid) produced higher transfection efficiency than Effectene (cationic lipids) or SuperFect (activated-dendrimer) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Transfection efficiencies have been reported in epithelial cells using PEI [17], PEI grafted N-maleated chitosan copolymers [18], nanostructured lipid carrier with cetylated PEI and Lipofectamine 2000 [19], cationic gemini lipids [20], and poly(disulfide amine)s [21]. A comparison study using lung tumor and normal epithelial cells showed that Lipofectamine 2000 (cationic lipid) produced higher transfection efficiency than Effectene (cationic lipids) or SuperFect (activated-dendrimer) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Graft copolymerization of chitosan with "presynthesized" polymers instead of their monomers can help to control the side-chain molar mass and avoid the absence of residual monomers. For example, Lu, Xu, Zhang, Cheng, and Zhuo (2008), prepared a chitosanbased copolymer, which had a good potential as efficient nonviral gene vectors, through grafting polyethylenimine (800 Da) to N-maleated chitosans. Kumar et al (2012) utilized polyacrylamide, instead of normal acrylamide monomer, for grafting onto chitosan with high grafting efficiency (GE¼92%) and grafting ratio (GR¼263%).…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…The results indicated that the chitosan-g-PEI (Figure 6b)/DNA complexes showed a higher transfection efficiency in three different cell lines than PEI 25K (M w ¼ 25 000) as a control. Lu et al [50] also grafted LMW-PEI to N-maleated chitosan (NMC-g-PEI). The NMC-g-PEI/ DNA complexes showed a higher transfection efficiency in 293T and HeLa cells than PEI 25K.…”
Section: Chitosan Derivativesmentioning
confidence: 99%